2003
DOI: 10.1046/j.1440-1754.2003.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary compliance with medication prescribed for paediatric patients discharged from a regional hospital

Abstract: : Primary compliance was suboptimal, with the majority of unfilled prescriptions being for antibiotics. These findings suggest that a remediable cause of treatment failure may be primary non-compliance with medication in regional settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A previous study of 65 patients also found a lack of significant association, but it may have been too small to detect a difference. 4 In larger studies, younger age has been associated with a higher likelihood of prescription filling 9,10,15 ; however, Beardon et al 10 defined the "younger age" pediatric group as patients ,15 years old. 10 Ekedahl and Månsson' s study 15 included children, but the number of children was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of 65 patients also found a lack of significant association, but it may have been too small to detect a difference. 4 In larger studies, younger age has been associated with a higher likelihood of prescription filling 9,10,15 ; however, Beardon et al 10 defined the "younger age" pediatric group as patients ,15 years old. 10 Ekedahl and Månsson' s study 15 included children, but the number of children was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 When children are discharged from the hospital with a prescription, up to 25% of prescriptions are not filled. 4 Prescription filling rates are similar or worse after emergency department (ED) visits. Claims data for adult ED prescriptions demonstrate that 16% to 25% of prescriptions are not filled.…”
mentioning
confidence: 99%
“…In the model, we also adjusted for differences in the non-adherence rate between different drug therapies [23-25]. "Short-term" drugs were categorised as the ATC-groups in which the average DDD/patient during the year 2006 was below 200 DDD.…”
Section: Methodsmentioning
confidence: 99%
“…However, variation in non-adherence can, to some extent, be explained by the type of drug or in terms of whether the patient's drug therapy is chronic or acute [22-25]. …”
Section: Introductionmentioning
confidence: 99%
“…A study by Wright et al found that only 75% of prescriptions for paediatric patients written in a regional Western Australian hospital were filled. 6 Patients over the age of 65 years are at an increased risk of medication misadventure particularly on discharge from hospital. 1,2 The aims of this study were to develop a survey tool to assess continuity of medication supply and provision of medicines information on discharge and to evaluate these parameters in patients discharged with either discharge medication or prescriptions for dispensing by a community pharmacy METHOD Pharmacy departments at one metropolitan teaching hospital and two rural hospitals (1 base, 1 district) participated in this study.…”
Section: Continuity Of Medication Supply and Provision Of Patient Infmentioning
confidence: 99%